FAM20C: A key protein kinase in multiple diseases - Rui Zhang; Yanming Ren; Yan Ju; Yuekang Zhang; Yan Zhang; Yuan Wang (Genes and Diseases)
Family with sequence similarity 20 C (FAM20C) is a Golgi protein kinase that phosphorylates the serine residue in the S-x-E/pS motif of target proteins. FAM20C phosphorylates most secreted proteins, which play important roles in multiple biological processes, including cancer progression, biomineralization, and lipid homeostasis. Numerous studies have documented the potential contribution of FAM20C to the growth, invasion, and metastasis of glioma, breast cancer, and other cancers, as well as to the mineralization process of teeth and bone. In addition, FAM20C has been found to be associated with the occurrence and development of certain cardiovascular diseases and endocrine metabolism disorders. It raises hopes that understanding the disease-specific mechanisms of FAM20C may hold the key to developing new strategies for these diseases. This review comprehensively covers the existing literature to provide a summary of the structure and biological functions of FAM20C, with a particular focus on its roles in the disease context.